Measuring Political Will and Political Constellation in Moving Indonesia’s Capital City Policy (Jurnal Bina Praja, 2023)
This research measuring how political will is in the policy of moving the national capital and how this policy is when faced with the existing political constellation. The type of research used is a qualitative approach. Methods of data collection using in-depth interviews and documentation techniques. The results of the research show that political will in the policy of moving the national capital cannot be separated from individual factors, namely the belief and courage of President Joko Widodo through a basis of reasoning that have strong relevance to empirical circumstances and are reflected through various regulations that have been stipulated. The organizational factor shows the government seriousness and commitment through the transition team formed, as a basis for working in a coordinated manner in achieving the targets set. The relationship factor shows the involvement of individuals/groups through the existence of various community supports, collaborative and partnerships, and the involvement of international figures in its implementation. Social factors show the dynamics of politics and condition of state apparatus in the decision-making process has reflected support for policies, seen from the agreement of the majority of political party factions, which at the same time has become strong political legitimacy. Overall, political will cannot be separated from the existing political constellation, the sustainability and success of the policy of moving the national capital will be determined by the next President leadership and the composition of the support of political parties that will come, which of course must have the same coherence of commitment.
Keywords: political will; political constellation; capital city; Nusantara